Perancangan Media Interaktif Berbasis Makromedia Flash Menggunakan Adobe Animate Pada Materi Teori Kinetik Gas - Alfiatun Hasanah; Maryani; Wildan Rochim; Melisa Febriyanti; Erika Chandhani; Lailliaytul Mukkaromah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the feasibility of interactive media based on Macromedia Flash on gas kinetic material and to determine the effectiveness of the product resulting from the development of interactive media based on Macromedia Flesh. This type of research is a literature review. This research uses descriptive research methods and uses a quantitative approach. The research subjects were 2 high school teachers and 10 students. The results of the research based on learning aspects and media aspects show a scale of 3-5, based on design aspects, content feasibility aspects and supporting aspects show a scale of 4-5. Based on the five aspects above, it shows a presentation of 66.7%, which means that the media is feasible to use. The test results on 10 students obtained student scores ≥70 on a scale of 10-100. From the test results of 10 students showed a percentage of 90% good level of understanding. So it can be concluded that this Macromedia Flash-based learning media is feasible to use.